2010
DOI: 10.1016/j.jtcvs.2010.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Cavopulmonary assist for the univentricular Fontan circulation: von Kármán viscous impeller pump

Abstract: Objectives In a univentricular Fontan circulation, modest augmentation of existing cavopulmonary pressure head (2–5 mmHg) would reduce systemic venous pressure, increase ventricular filling, and thus, substantially improve circulatory status. An ideal means of providing mechanical cavopulmonary support does not exist. We hypothesized that a viscous impeller pump, based on the von Kármán viscous pump principle, is optimal for this role. Methods A 3-dimensional computational model of the total cavopulmonary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 24 publications
1
89
0
1
Order By: Relevance
“…Previous reports have focused on mechanical assistance of this failing circulation by use of subpulmonary blood pumps to drive blood forwards through the pulmonary circuit [4, 5, 1014] or with a viscous impeller pump based on the Von Karman principle [3, 15]. Although there has been clinical success [10] with this approach of pushing blood through the pulmonary circuit, significant surgical modifications to the existing cavopulmonary circuit are required to implement this strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have focused on mechanical assistance of this failing circulation by use of subpulmonary blood pumps to drive blood forwards through the pulmonary circuit [4, 5, 1014] or with a viscous impeller pump based on the Von Karman principle [3, 15]. Although there has been clinical success [10] with this approach of pushing blood through the pulmonary circuit, significant surgical modifications to the existing cavopulmonary circuit are required to implement this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to support the single ventricle circulation mechanically have suggested that a custom-built assist device is needed to push [ 35] rather than pull through the pulmonary circulation. We hypothesized that using a conventional ventricular assist device, with or without conversion of a total cavopulmonary connection to a bidirectional Glenn cavopulmonary connection would allow assistance by pulling blood through the circuit and improve cardiac index (CI).…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] An ideal Fontan assist device/cavopulmonary assist device would provide equal continuous flow at a low-pressure head to avoid lung perfusion injury, would be resilient to afterload to overcome elevated and possibly fluctuating pulmonary vascular resistance, and would avoid inlet suction within the Fontan pathway in the absence of a venous reservoir. Rodefeld et al 27 have developed a pediatric transcatheter-expandable impellar pump that is positioned at the crux of the cavopulmonary junction and directs flow into both lungs. Although this device is still far from clinical application, significant strides have been made in understanding the unique anatomic and physiological constraints of total cavopulmonary connection circulation, with the hope of a durable assist device on the horizon.…”
Section: Expanding Vad Support To Challenging Pediatric Populationsmentioning
confidence: 99%
“…15 In Fontan physiology, there is a relative increase in systemic venous pressure and decrease in pulmonary arterial pressure (Fontan paradox). 4 A partial assist device in the TCPC pathway which can provide 2-5 mmHg pressure augmentation will simultaneously reduce systemic venous pressure and increase pulmonary arterial pressure to restore conditions more closely resembling a more stable two ventricle circulation.…”
Section: Introductionmentioning
confidence: 99%
“…15 An expandable viscous impeller pump (VIP), based on the von Ka´rma´n viscous pump principle, appears to satisfactorily address these problems. The application of the VIP to the Fontan is defined here as Powered Fontan.…”
Section: Introductionmentioning
confidence: 99%